Determinant of Smoking Behavior among Childbearing Age Women in Indonesia - Laksono, Agung Dwi; Rukmini Rukmini,; Wulandari, Ratna Dwi (International Journal of Psychosocial Rehabilitation, 2020)
Tobacco smoking behavior in women is a major cause of fertility problems, the reproductive system, and many other health problems. The study aimed to analyze the determinant of smoking behavior among childbearing age women in Indonesia. The samples used were a childbearing woman. The sample size was 86,239 women. The variables analyzed included type of place of residence, age group, education level, employment status, marital status, wealth status, health insurance, parity, and currently pregnant. Determination of determinant by binary logistic regression. The study results inform that the more educated a woman was, the less likely she was to be a smoker. Childbearing age women who were employed were 1.177 times more likely to smoke than not employed women. Childbearing age women who have wealth status of the richest category were 0.661 times more likely to smoke than the poorest women. Wealth status was an inhibiting factor for smoking behavior. Childbearing age women who were covered by health insurance were 0.831 times more likely to smoke than women who were not covered by health insurance. Multiparous women were 1.252 times more likely to smoke than primiparous women. Five variables were determinants of smoking behavior among childbearing age women in Indonesia, i.e. education level, employment status, wealth status, health insurance, and parity.